Uma ameaça de guerra no fim do mundo : a política externa da administração Carter diante da questão do Canal de Beagle (1977-1980) - Gaziero, Gabriel (2021)
This research sought to explore U.S. foreign policy on the Beagle Channel affair, a territorial dispute between the Argentine and Chilean dictatorships for the channel region and its islands in Tierra del Fuego, that almost led to a war in the end of 1978. Through documents from the U.S. Department of State and U.S. embassies in Buenos Aires and Santiago, we developed a research that sought to unveil the foreign policy of democrat president Jimmy Carter (1977-1980) for this specific conflict and also to identify the relations between it and the other more general U.S. objectives in the region like human rights and even the Cold War, which gains importance especially after 1979 with the Soviet invasion of Afghanistan. In our content-analysis of the documents available we studied: the administration’s strategic interests in the South Atlantic narrows and passages; the close attention given to the developments in bilateral negotiations; the actions taken during the Crisis in December 1978; the progress (or lack of) of the papal mediation in Rome; and also the decisions and disputes inside the administration itself that took into account the Beagle Channel situation as an element in policy making for Argentina and Chile in general, taking into consideration its relevance when associated with correlated issues. The interests connected with the Beagle Channel affair encompass regional balance of power, hemispheric stability and the effects of the human rights policy in bilateral relations and U.S. influence over both governments, including its capacity to press for a peaceful resolution in the Beagle conflict. The human rights issue gains special prominence when dealing with the Southern Cone’s National Security dictatorships once the region was in the epicentre of the Carter administration's efforts, in part, due to its low political cost for U.S. general interests. Based on this study, we conclude that beyond having a general importance in the making of foreign policy to Argentina and Chile, the Beagle Channel matter reinforced the internal debate about the consequences of the use of sanctions and restrictions based on human rights in Argentina and Chile throughout the 1970’s. In this sense, the Beagle joined other U.S. interests that were used as arguments by those inside the administration that wanted to rebuild US relations with both countries and questioned the approach adopted by the government.